The Effectiveness of the 5E Instructional Model on the Academic Achievement of 9th Grade Students Towards Learning English Reading Comprehension Skills - Tarawneh, Majid (Dirasat: Human and Social Sciences, 2024)
Objectives: Assessing the effectiveness of the 5E Instructional Model on the academic achievement of 9th grade students towards learning English’s reading comprehension skills at the Model School of The University of Jordan. Methods: Administering pre-and post-tests to both control and experimental groups. Each group consisted of 25 students. Both groups were assigned reading lessons for six weeks with two different instructional methods i.e., the direct method and the 5E Instructional Model. Results: The results of the post-achievement test showed a statistically significant difference between the average scores of the experimental group (10.24 ±1.1) and the control group (7.24 ± 0.07) and therefore, the E5 educational model appeared more efficient in improving students' academic achievement compared to the direct teaching method. Conclusions: The study concludes that the E5 educational model enables students to learn and develop their reading comprehension skills by using their prior knowledge, explore new ideas and questions, self-examination and reflection.